AI-Based Learning System In Analyzing Student Progress In Real-Time - Ahmad Tegar Fauzan; Rivan Saghita Pratama; Sheva Tiara Kasih Elda (Physical Activity Journal (PAJU), 2025)
This study aims to analyze the usage of AI in the learning system to analyze student progress in real-time. The method utilized is a narrative literature review, which is divided into two stages: collecting and analyzing data. Data was collected by examining 25 articles from various sources. Data analysis through topic-based categorization in AI-driven learning systems is employed to monitor and evaluate student progress in real time. The results of the narrative literature review reveal that AI has great potential in increasing the effectiveness and personalization of learning. However, it also poses challenges like the digital divide and ethical issues. In conclusion, implementing AI in education requires a holistic and sustainable approach to maximize its benefits and address its challenges.